Kolaborasi Akademisi, Mahasiswa, dan Relawan Dalam Tanggap Darurat Bencana Banjir Aceh Tamiang: Model Distribusi Bantuan Berbasis Participatory Action Research - Dori Chandra; Karo, TIY Kusmarrabbi; Taufik Hidayat; Indra, Indra; Andri Rivai; Ritonga, Ade Muhammad (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
The floods that hit Aceh Tamiang Regency, Nanggroe Aceh Darussalam Province in November 2025 have seriously affected people's lives. Thousands of homes were submerged, access roads were cut off, infrastructure was damaged, and it's been hard to supply people's basic needs. This emergency situation requires a quick and coordinated response from various parties, including colleges and universities. This community service project aims to provide humanitarian assistance to flood victims through the distribution of basic food supplies, medicines, and other essential items. The partners in this community service project are the flood-affected communities in four locations (Buluh Butung Village, Purwodadi, Kota Lintang Bawah, and Landu) and the Aceh Tamiang Regional General Hospital. The method used is adapted from the principles of participatory action research, which includes team coordination, fundraising, procurement of aid, and distribution through direct delivery, assembly points, and door-to-door visits. The implementation team consisted of 42 people (7 lecturers, 5 students, and 30 volunteers) who successfully raised Rp 138,500,000. The activities were carried out on 5 and 8 November 2025 at five distribution points. The results of the community service programme show that 270 households (approximately 855 people) successfully received assistance in the form of 250 food packages, hundreds of bales of clothing, thousands of medicines and medical supplies, and other essential items. The community responded very positively with great enthusiasm, and the distribution ran smoothly. Feedback from beneficiaries indicated that the food parcels and medicines were highly effective in providing basic necessities, although there were still ongoing needs such as emergency tents, sleeping equipment, and water storage containers. This community service initiative demonstrated the importance of collaboration between colleges or universities, students, and volunteers in rapid disaster response, as well as the effectiveness of multi-location distribution adjusted to actual conditions on the ground.